PERBANDINGAN ALGORITMA MINIMAX DAN NEGASCOUT PADA PERMAINAN CATUR SEDERHANA - David David (Mulawarman University, 2013)
Simple Chess is a board game played by two players using boards sized in 3 rows and 3 columns and each player has pawns with different colors (normally black and white). The player wins if he/she can arrange the pawns in one line (diagonal, vertical or horizontal). The writer makes the comparisons of negascout algorithm and minimax algorithm in the application of Simple Chess to maximize the more suitable algorithm and implement them on the pawn placements in the shortest time. This research applies experimental method in form of literature study. The aspects of this research cover required features such as interface, input validation and output design. The result of this design is the application of Simple Chess embedded in negasc out algorithm and minimax algorithm. The tests used by White Box are Input, Output, program functions, and the speed of negascout algorithm and minimax algorithm in the pawn placements in Simple Chess. After being tested, the result shows that each algorithm has its own advantages and disadvantages, in which tests are done through pawn placements with the fastest time. After the comparison tests are finished, the writer concludes that in this research, minimax algorithm has a better pawn movement time in placements, whereas negascout algorithm has a better step decision.